2017
DOI: 10.7554/elife.30668
|View full text |Cite
|
Sign up to set email alerts
|

Live imaging of heart tube development in mouse reveals alternating phases of cardiac differentiation and morphogenesis

Abstract: During vertebrate heart development, two progenitor populations, first and second heart fields (FHF, SHF), sequentially contribute to longitudinal subdivisions of the heart tube (HT), with the FHF contributing the left ventricle and part of the atria, and the SHF the rest of the heart. Here, we study the dynamics of cardiac differentiation and morphogenesis by tracking individual cells in live analysis of mouse embryos. We report that during an initial phase, FHF precursors differentiate rapidly to form a card… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 68 publications
1
71
1
1
Order By: Relevance
“…Over a well-defined developmental window, multi-potent, latedifferentiating progenitors of the SHF migrate into the poles of the heart tube to extensively remodel and add structure to the heart (Cai et al, 2003;van den Berg et al, 2009;Hutson et al, 2010;Kelly, 2012). It remains under debate, however, whether the FHF and SHF represent truly distinct populations with unique molecular signatures, or whether they exist as one population with a gradient in timing for deployment to the heart (Abu-Issa et al, 2004;Moorman et al, 2007;Ivanovitch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Over a well-defined developmental window, multi-potent, latedifferentiating progenitors of the SHF migrate into the poles of the heart tube to extensively remodel and add structure to the heart (Cai et al, 2003;van den Berg et al, 2009;Hutson et al, 2010;Kelly, 2012). It remains under debate, however, whether the FHF and SHF represent truly distinct populations with unique molecular signatures, or whether they exist as one population with a gradient in timing for deployment to the heart (Abu-Issa et al, 2004;Moorman et al, 2007;Ivanovitch et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…4A). These further developed into denser crescent-like structures with beating areas, leading to beating epithelial protrusions on the anterior portion of the gastruloids at around 168 h. Similar to mouse embryos (Ivanovitch et al, 2017;Le Garrec et al;Tyser et al, 2016), these phenotypes could be observed in gastruloids within 24 h, and could be aligned to progressive morphological stages of embryonic cardiac development between E7.5 and E8.5 (Fig. 4B).…”
Section: In Vitro Cardiac Development Occurs Through Establishment Ofmentioning
confidence: 62%
“…4D,E, Supplemental Movie 5). This is reminiscent of the spatial arrangement of anterior structures in the developing embryo (Ivanovitch et al, 2017).…”
Section: In Vitro Cardiogenesis Happens In the Context Of Physiologicmentioning
confidence: 96%
See 1 more Smart Citation
“…Regardless, while both the mouse and human micropattern platforms described above are perfect examples of the value of engineering approaches to development, in vivo cell fate specification and morphogenesis are heavily dependent on the 3D context of the developing embryo. In vivo development involves folding of tissues (e.g., neural, gut, or heart tube development) (Ivanovitch et al, 2017;Nikolopoulou et al, 2017;Spence et al, 2011), tissue migration and intercalation (e.g., gastrulation, notochord morphogenesis; Balmer et al, 2016;Rivera-Pé rez and Hadjantonakis, 2014;Viotti et al, 2014), and compartmentalization of soluble signals and their receptors (Zhang et al, 2018b). Understandably, these are features that cannot all be recapitulated by monolayer systems.…”
Section: Recapitulating Early Mammalian Development In Vitromentioning
confidence: 99%